The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.5194/acp-9-8531-2009
|View full text |Cite
|
Sign up to set email alerts
|

What drives the observed variability of HCN in the troposphere and lower stratosphere?

Abstract: Abstract.We use the GEOS-Chem global 3-D chemistry transport model to investigate the relative importance of chemical and physical processes that determine observed variability of hydrogen cyanide (HCN) in the troposphere and lower stratosphere. Consequently, we reconcile groundbased FTIR column measurements of HCN, which show annual and semi-annual variations, with recent space-borne measurements of HCN mixing ratio in the tropical lower stratosphere, which show a large two-year variation. We find that the ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 50 publications
2
57
0
Order By: Relevance
“…They also agree well with HCN columns observed at mid-latitude regions, as in northern Japan at 44 • N in 1995 (Zhao et al, 2000) as well as at Jungfraujoch from 2001 to 2009 (Li et al, 2009). In addition, our extreme values, exceeding 10 × 10 15 molecules cm −2 in summer 2010, are comparable to values found in the tropics at Reunion Island during the biomass burning seasons from 2004 to 2011 .…”
Section: Discussionsupporting
confidence: 78%
“…They also agree well with HCN columns observed at mid-latitude regions, as in northern Japan at 44 • N in 1995 (Zhao et al, 2000) as well as at Jungfraujoch from 2001 to 2009 (Li et al, 2009). In addition, our extreme values, exceeding 10 × 10 15 molecules cm −2 in summer 2010, are comparable to values found in the tropics at Reunion Island during the biomass burning seasons from 2004 to 2011 .…”
Section: Discussionsupporting
confidence: 78%
“…In summary, we think the apparent biennial cycle is caused by interannual variations in biomass burning and does not have a direct meteorological reason beyond the effect of meteorology on the biomass burning itself. This assumption is corroborated by GEOS-Chem model calculations of Li et al (2009), who found that the interannual differences of HCN amounts in the tropical troposphere and lower stratosphere are much more strongly controlled by variations in biomass burning than by the meteorology.…”
Section: The Tropical Hcn Tape Recordersupporting
confidence: 68%
“…In subsequent publications these observations have been compared with model runs. Li et al (2009) used groundbased HCN column amounts as well as MLS and ACE-FTS data to constrain the GEOS-Chem model, which resulted in annual and semi-annual variations in the upper troposphere but consecutive 2-year cycles of the HCN anomaly in the lower stratosphere. Their model runs indicated that the 2-year tape recorder cycle is caused by the extent of temporal overlap of biomass burning in Africa and other regions, particularly Indonesia, Australia and South America.…”
Section: Introductionmentioning
confidence: 99%
“…BB is considered to be the major source of HCN in the atmosphere (Li et al, , 2009Liang et al, 2007;Shim et al, 2007) via the pyrolysis of N-containing species within the fuel (Johnson and Kang, 1971;Glarborg et al, 2003). Cooking fire emissions of HCN have also been observed in Mexico and Africa (Christian et al, 2010), although concentrations fell below Fourier transform IR (FTIR) detection limits.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass burning (BB) is considered to be a major source of trace gases in the atmosphere (Li et al, , 2009Shim et al, 2007) and at levels significant enough to perturb regional and global atmospheric chemistry and composition (Levine, 2000). For example, large boreal forest fires in Russia from 2002 to 2003 were responsible for global growth rates of many trace gases including carbon dioxide and methane (Kasischke et al, 2005;Yurganov et al, 2005;, but also to contribute to climate change (Damoah et al, 2004;Vivchar et al, 2010;Tilmes et al, 2011).…”
Section: Introductionmentioning
confidence: 99%